Correction: Correction: Multi-scale microporous silica microcapsules from gas-in water-in oil emulsions. Issue 1 (16th December 2020) - Toprakcioglu, Zenon; Hakala, Tuuli A.; Levin, Aviad; Becker, Christian F. W.; Bernardes, Gonçalo J. L.; Knowles, Tuomas P. J.
Abstract : Correction for 'Correction: Multi-scale microporous silica microcapsules from gas-in water-in oil emulsions' by Zenon Toprakcioglu et al., Soft Matter, 2020, 16, 3586–3586, DOI: ; 10.1039/D0SM90059A .